# Implement With Types, Not Your Brain!

When asked about the virtues of Haskell’s strong type system, most people will say the best part is that it lets you refactor with a zen-like tranquility, or that it stops your program from crashing at runtime. I mean, those are both great. But my favorite part is that having a strong type system means I don’t need to use my brain to do programming.

It sounds snide, but it’s true. Here’s a function from my library polysemy:

hoistStateIntoStateT
:: Sem (State s ': r) a
-> S.StateT s (Sem r) a
hoistStateIntoStateT (Sem m) = m $\u -> case decomp u of Left x -> S.StateT$ \s ->
liftSem . fmap swap
. weave (s, ())
(\(s', m') -> fmap swap
$S.runStateT m' s') (Just . snd)$ hoist hoistStateIntoStateT x
Right (Yo Get z _ y _)     -> fmap (y . (<$z))$ S.get
Right (Yo (Put s) z _ y _) -> fmap (y . (<$z))$ S.put s

Gee, that’s complicated! I must be really smart to have written such a function, right?

Wrong! I just have a trick!

The technique is called “just use type holes,” and for my money, it’s the most important skill in a Haskeller’s tool-belt. The idea is to implement the tiny part of a function that you know how to do, and then ask the compiler for help on the rest of it. It’s an iterative process. It’s a discussion with the compiler. Each step of the way, you get a little closer to the right answer, and after enough iterations your function has written itself — even if you’re not entirely sure how.

Let’s go through an example together. Consider the random type signature that I just made up:

jonk :: (a -> b) -> ((a -> Int) -> Int) -> ((b -> Int) -> Int)

If you want a challenge, take a few minutes to try to implement this function. It’s tricky, and most people get lost along the way. When you’re convinced that it’s sufficiently hard, continue reading.

The first step of writing a function is to bind all of the variables we have. That’s the a -> b and (a -> Int) -> Int bits here. I usually give them names that help me remember their types — such as ab and aii, respectively.

Then, bang out a _ on the right hand side. This thing is a placeholder, and is called a type hole.

jonk ab aii = _

Try to compile this (consider using something like ghcid so you don’t need to call ghc by hand.) The compiler will yell at you:

    • Found hole: _ :: (b -> Int) -> Int
Where: ‘b’ is a rigid type variable bound by
the type signature for:
jonk :: forall a b.
(a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
at /home/sandy/Test.hs:3:1-62
• In the expression: _
In an equation for ‘jonk’: jonk ab aii = _
• Relevant bindings include
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)
|
4 | jonk ab aii = _
|

A common complaint from beginners is that GHC’s error messages are noisy. This is true. To a first approximation, the useful bit of this error message is this:

• Found hole: _ :: (b -> Int) -> Int
• Relevant bindings include
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)

There’s no way of getting GHC to shut up about that other stuff, so you just need to train yourself to focus on this core piece of information. That’s not to say the other stuff isn’t helpful, just that this stuff is almost always enough.

So what is the compiler telling us? Two things:

1. The expression we want to replace _ with must have type (b -> Int) -> Int.
2. We have some local binds (aii, ab, jonk, and their types) that we can use to help with the implementation.

Using this information, our goal is to write the correct expression in place of the type hole. In most cases doing that in one step is unfeasible, but we can often write a little more of expression, and use a type hole in that.

In this case, we notice that our hole has type (b -> Int) -> Int, which is to say, that it’s a function that takes a (b -> Int) and returns an Int. As such, it means we should bind the (b -> Int) in a lambda:

jonk ab aii = \bi -> _

The resulting error message in full is this:

    • Found hole: _ :: Int
• In the expression: _
In the expression: \ bi -> _
In an equation for ‘jonk’: jonk ab aii = \ bi -> _
• Relevant bindings include
bi :: b -> Int (bound at /home/sandy/Test.hs:4:16)
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)
Valid hole fits include
maxBound :: forall a. Bounded a => a
with maxBound @Int
(imported from ‘Prelude’ at /home/sandy/Test.hs:1:1
(and originally defined in ‘GHC.Enum’))
minBound :: forall a. Bounded a => a
with minBound @Int
(imported from ‘Prelude’ at /home/sandy/Test.hs:1:1
(and originally defined in ‘GHC.Enum’))
|
4 | jonk ab aii = \bi -> _
|

GHC now mentions “Valid hole fits”. In my experience, these are almost always useless, so I just exclude them. In GHCi, the following incantation will make them disappear.

:set -fmax-valid-hole-fits=0

(or you can just squint and ignore them manually!)

Again, ignoring the irrelevant pieces of the error message, we can pare GHC’s response down to this:

• Found hole: _ :: Int
• Relevant bindings include
bi :: b -> Int (bound at /home/sandy/Test.hs:4:16)
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)

OK, great! Now we just need to produce an Int. While we could just put 0 here, that is a clearly wrong solution, since we wouldn’t be using any of ab, aii or bi. Don’t just return 0.

But we notice that both aii and bi will return an Int. Since that’s what we want to return, the odds are good that we want to call one of these functions in this hole. Let’s choose aii as a guess. Feel free to write in your notebook that you are guessing about aii, but also bi could have been chosen — we have no guarantees that aii is the right call!

jonk ab aii = \bi -> aii $_ • Found hole: _ :: a -> Int • Relevant bindings include bi :: b -> Int (bound at /home/sandy/Test.hs:4:16) aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9) ab :: a -> b (bound at /home/sandy/Test.hs:4:6) jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int (bound at /home/sandy/Test.hs:4:1) Our hole has a function type, so let’s introduce a lambda: jonk ab aii = \bi -> aii$ \a -> _
• Found hole: _ :: Int
• Relevant bindings include
a :: a (bound at /home/sandy/Test.hs:4:29)
bi :: b -> Int (bound at /home/sandy/Test.hs:4:16)
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)

We need to produce an Int again. Since we don’t have one in scope, our only options are again aii and bi. But we’ve already used aii, so let’s try bi this time.

jonk ab aii = \bi -> aii $\a -> bi$ _
• Found hole: _ :: b
• Relevant bindings include
a :: a (bound at /home/sandy/Test.hs:4:29)
bi :: b -> Int (bound at /home/sandy/Test.hs:4:16)
aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9)
ab :: a -> b (bound at /home/sandy/Test.hs:4:6)
jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int
(bound at /home/sandy/Test.hs:4:1)

Great! Now we need to produce a b. We have a function that can do that, ab :: a -> b. So let’s call that:

jonk ab aii = \bi -> aii $\a -> bi$ ab $_ • Found hole: _ :: a • Relevant bindings include a :: a (bound at /home/sandy/Test.hs:4:29) bi :: b -> Int (bound at /home/sandy/Test.hs:4:16) aii :: (a -> Int) -> Int (bound at /home/sandy/Test.hs:4:9) ab :: a -> b (bound at /home/sandy/Test.hs:4:6) jonk :: (a -> b) -> ((a -> Int) -> Int) -> (b -> Int) -> Int (bound at /home/sandy/Test.hs:4:1) Finally, we have a hole whose type is a. And we have an a! Let’s just use that thing! jonk ab aii = \bi -> aii$ \a -> bi $ab$ a
[1 of 1] Compiling Main             ( /home/sandy/Test.hs, interpreted )
Ok, one module loaded.

Cool! It worked! We just wrote a non-trivial function without doing any thinking, really. Not bad! But can we be confident that our implementation is any good?

The first line of defense against this is to enable -Wall. In GHCi, you can do this via:

:set -Wall

You’ll notice there are no warnings generated by our definition. This is usually enough of a sanity check that our implementation is fine. For example, let’s see what happens when we try the obviously stupid implementation:

jonk ab aii = \bi -> 0
/home/sandy/Test.hs:4:6: warning: [-Wunused-matches]
Defined but not used: ‘ab’
|
4 | jonk ab aii = \bi -> 0
|      ^^

/home/sandy/Test.hs:4:9: warning: [-Wunused-matches]
Defined but not used: ‘aii’
|
4 | jonk ab aii = \bi -> 0
|         ^^^

/home/sandy/Test.hs:4:16: warning: [-Wunused-matches]
Defined but not used: ‘bi’
|
4 | jonk ab aii = \bi -> 0
|

Those warnings are pointing out that we haven’t used everything available to us. If we assume that the type of jonk is correct, then any implementation of jonk which doesn’t use all of its variables is extremely suspect.

The other common way to go wrong here is that you’ll notice that jonk comes up in the relevant bindings while trying to write jonk. For example, this thing will happily typecheck:

jonk = jonk

But this too is clearly wrong, since we haven’t done any work. The situation becomes more insidious when you call yourself recursively after doing some work, which can be correct. Let’s look at an example of that.

Let’s try this type on for size:

zoop :: (a -> b -> b) -> b -> [a] -> b

The first thing to do is to bind all of our variables:

zoop abb b as = _

But we notice that as has type [a]. Since [a] has two constructors, let’s pattern match on those before going any further.

zoop abb b []       = _
zoop abb b (a : as) = _
• Found hole: _ :: b
• Relevant bindings include
b :: b (bound at /home/sandy/Test.hs:4:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:4:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

• Found hole: _ :: b
• Relevant bindings include
as :: [a] (bound at /home/sandy/Test.hs:5:17)
a :: a (bound at /home/sandy/Test.hs:5:13)
b :: b (bound at /home/sandy/Test.hs:5:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:5:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

Oh god! Too many holes at once. My brain is already exploding. You honestly expect me to keep this much information in my head at once?? Instead, we can replace one of the holes with undefined in order to get GHC to shut up and let us focus.

zoop abb b []        = _
zoop abb b (a : as) = undefined
• Found hole: _ :: b
• Relevant bindings include
b :: b (bound at /home/sandy/Test.hs:4:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:4:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

Much easier. We see that we need to produce a b, and hey, look at that. We already have one. Furthermore, we don’t have an a, and so we have no chance of calling abb. So we assume b is correct. Let’s fill it in, and then replace our undefined with a hole again:

zoop abb b []       = b
zoop abb b (a : as) = _
• Found hole: _ :: b
• Relevant bindings include
as :: [a] (bound at /home/sandy/Test.hs:5:17)
a :: a (bound at /home/sandy/Test.hs:5:13)
b :: b (bound at /home/sandy/Test.hs:5:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:5:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

Again we want to produce a b. We could use the b we have, but that would mean abb is completely unused in our function. So let’s assume we want to call abb instead. Since it takes two arguments, let’s give the first one a hole, and the second undefined. One step at a time.

zoop abb b []       = b
zoop abb b (a : as) = abb _ undefined
• Found hole: _ :: a
• Relevant bindings include
as :: [a] (bound at /home/sandy/Test.hs:5:17)
a :: a (bound at /home/sandy/Test.hs:5:13)
b :: b (bound at /home/sandy/Test.hs:5:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:5:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

We want an a. And we have an a. Since we have no guarantees that as isn’t [], this a is our only choice. So it’s pretty safe to assume our hole should be filled with a.

zoop :: (a -> b -> b) -> b -> [a] -> b
zoop abb b []       = b
zoop abb b (a : as) = abb a _
• Found hole: _ :: b
• Relevant bindings include
as :: [a] (bound at /home/sandy/Test.hs:5:17)
a :: a (bound at /home/sandy/Test.hs:5:13)
b :: b (bound at /home/sandy/Test.hs:5:10)
abb :: a -> b -> b (bound at /home/sandy/Test.hs:5:6)
zoop :: (a -> b -> b) -> b -> [a] -> b
(bound at /home/sandy/Test.hs:4:1)

So we need to produce a b, and we still have the unused as :: [a] to work with, so it’s unlikely to just be our binding b. Instead, our only option which takes a [a] is zoop itself! This is a recursive call, but we’ve already popped the head off our list, so it’s not going to be an infinite loop.

Lets fill in our hole with zoop _ _ as. Or, zoop _ undefined as if you prefer.

zoop abb b []       = b
zoop abb b (a : as) = abb a $zoop _ undefined as • Found hole: _ :: a -> b -> b • Relevant bindings include as :: [a] (bound at /home/sandy/Test.hs:5:17) a :: a (bound at /home/sandy/Test.hs:5:13) b :: b (bound at /home/sandy/Test.hs:5:10) abb :: a -> b -> b (bound at /home/sandy/Test.hs:5:6) zoop :: (a -> b -> b) -> b -> [a] -> b (bound at /home/sandy/Test.hs:4:1) Probably abb, because we’re recursing, and have no real reason to want to change this function. Fill it in, and, for the same argument, replace our undefined with b. Our final function in all its glory is this: zoop :: (a -> b -> b) -> b -> [a] -> b zoop abb b [] = b zoop abb b (a : as) = abb a$ zoop abb b as

And it works! Except that -Wall yells at us:

/home/sandy/Test.hs:4:6: warning: [-Wunused-matches]
Defined but not used: ‘abb’
|
4 | zoop abb b []       = b
|

This is a little alarming, until we realize that abb isn’t not used in zoop, it’s just not used in this branch. We can put a wildcard to match abb here to get rid of this warning:

zoop :: (a -> b -> b) -> b -> [a] -> b
zoop _   b []       = b
zoop abb b (a : as) = abb a \$ zoop abb b as

(note that this _ on the left-hand side of the equals sign is not a type hole, it’s a wildcard pattern match!)

Finally we’re finished! A little experimentation will convince you that this zoop thing we just wrote is in fact just foldr! Pretty impressive for just blindly filling in holes, no?

I’m not going to say that blindly filling in type holes always works, but I’d say maybe 95% of the time? It’s truly amazing just how far you can get by writing down the right type and making sure you use every variable.

The reason why this works is known as theorems for free, which roughly states that we can infer lots of facts about a type signature (assuming it’s correct.) One of those facts we can infer is often the the only possible implementation. It’s cool as fuck, but you don’t need to understand the paper to use this idea in practice.

One question you might have is “what the heck does it mean for a type to be correct?” Good question! It means your type should be as polymorphic as possible. For example, if you want a function that creates a list with length $n$, where all elements are the same value, then that thing should have type Int -> a -> [a], not Int -> Bool -> [Bool]. Because we can do this operation for any type, we don’t need to give it a monomorphic type. Here we would say Int -> a -> [a] is the correct type for this operation, while Int -> Bool -> [Bool] is not.

You know when people say “types are not an alternative to documentation?” I think this is a pretty knock-down argument to that claim. Once you really understand the typesystem, most of the time, types really are the best documentation — they often tell you exactly what the function does, in a way that English comments never will.

In conclusion, a strong type system is fucking awesome because it’s smart enough to know the necessary type of any given expression. Which means you can slowly use type holes to chip away at a difficult implementation, without ever really knowing what you’re doing. It’s marvelous. Get into the habit of using this technique, and you’ll quickly be amazed at just how good you get at Haskell.